Luminescent properties of complexly substituted oxides Ме2Ln8 (XO4)6O2 (Me=Sr, Ca; Ln=La, Gd, Eu; X= Si, P) - A. A. Vasin; M. G. Zuev (Chimica Techno Acta, 2014)
In the current work it is established that the maximum intensity of a luminescence of crystalline phosphors with structure silicate-apatite of general formulae: Ca2Eu8Si6(1-x)P6xO26, Sr2Gd7.2Eu0.8Si6(1-x)P6xO26 and Ca2La8(1-x)Eu8xSi6O26 is reached at concentration of europium equal 0,15. The maximum intensity of a luminescence of these substances, at replacement in an anion sublattice of tetrahedrons [SiO4]4- on tetrahedrons [PO4]3- takes place at concentration of phosphorus 0,05.